Correlation of Leukocyte and Lymphocyte Counts With Positive Tubex Scores in Pediatric Typhoid Fever Patients - Galuh Hutami Kuncahyono; Eka Airlangga (Fakultas Kedokteran Universitas Malikussaleh, 2025)
Typhoid fever or enteric fever is a systemic infectious disease caused by Salmonella Typhi and Salmonella Paratyphi, which remains a major cause of morbidity and mortality in developing countries. A large proportion of typhoid fever cases occur in patients aged ≤19 years. Bacterial endotoxins may alter hematological parameters such as leukocyte and lymphocyte counts, while hematological and Tubex examinations facilitate rapid diagnosis. This study aimed to determine the correlation between leukocyte and lymphocyte counts with Tubex positive scores in pediatric typhoid fever patients. An observational analytical study with a cross-sectional design and retrospective approach was conducted using medical records of pediatric typhoid fever patients at RSU Haji Medan. The majority of patients were aged ≥5 years (80.5%), male (53%), with a length of stay <7 days (92.7%), and a Tubex positive score (≥+6) (65.9%). Among patients aged <5 years, most had normal leukocyte counts (51.6%) and lymphocytosis (41.9%), while in patients aged ≥5 years, most had normal leukocyte counts (63.9%) and lymphocytopenia (46.6%). Bivariate analysis showed no significant correlation between leukocyte counts and Tubex positive scores in both <5 years (p=0.257) and ≥5 years (p=0.422) groups. However, a significant correlation was found between lymphocyte counts and Tubex positive scores in patients aged ≥5 years (p=0.009). In conclusion, lymphocyte counts are significantly correlated with Tubex positive scores in pediatric typhoid fever patients aged ≥5 years, suggesting their potential role as supportive diagnostic parameters.